Verified assumptions of the economic theory of whirlpools - Juzwiszyn, Jacek (Zweryfikowane założenia ekonomicznej teorii wirów, 2010)
Three-dimensional vibrations of economic vectors always take place around the hypothetical line of the economic equilibrium. The geometrical observation of the kinematics of the course of stock exchange occurrences originated the so called technical analysis, which among other activities seeks new rules in order to be able, with their help, to appoint occurrences of so called turning points on capital markets, or to fix time horizons of appearing trends, etc. In the sequence of several dozen recent years the methods using twodimensional spirals (price and time) have experienced a few interesting alterations. It seems that the research of capital helices should be continued, since the very process of whirling of vectors will last as long as the ones participating in the market will be undertaking the decisions in terms of the price and quantity, concerning the purchase (or sale) of vectors.
Mathematical Economics, 2010, Nr 6 (13), s. 49-64
Keywords: golden ratio; vortex movement; logarithmic helix; modified cobweb model